TINJAUAN TEORITIS WEWENANG DPR DALAM PENETAPAN DAN PENGAWASAN APBN BERDASARKAN PASAL 23 UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Nanik Ida Rosini (Jurnal Surya Kencana Satu : Dinamika Masalah Hukum dan Keadilan, 2016)
The purpose of this research is to know and understand the source of authority of the House of Representatives (DPR) in setting the state budget and to know and understand whether the authority of the House of Representatives (DPR) as a legislative institution in accordance with the Constitution of the Republic of Indonesia in 1945 in the establishment and supervision Budget relating to financial managemen. this is normative Reaserch Method, which uses materials such law; legislation as primary law; legal theories, research, writing (the work) of the legal scholars and other written legal documents that are relevant to the object of research and other written documents relevan.Dalam order to realize good governance in the running state government, since a few years ago have been implemented Government Financial Management reform. Research shows first, the reform: getting a strong legal basis with the enactment of Law No. 17 Year 2003 on State Finance, Law No. 1 of 2004 on State Treasury and Law No. 15 of 2004 on Management and Financial Responsibility State, second, organize the separation of functions of state financial management officer consisting of: the Minister of Finance as the Manager of Finance and the State General Treasurer, while the leadership of the Ministry / Agency as Budget User. Keywords: Authority, Supervision Budget, State Financial Management Officer